Bibliometric analysis of research on social entrepreneurship - Nurul Aziza; M. Adhi Prasnowo; Nurmawati Nurmawati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to identify research trends and patterns in the field of social entrepreneurship.Method — We employed a descriptive bibliometric analysis methodology to identify publications related to social entrepreneurship between 2020 and 2022. Using the Scopus database, we conducted data collection by utilizing the keyword